SISTEM PENGENDALIAN INTERNAL DALAM MENUNJANG EFEKTIVITAS PEMBERIAN KREDIT USAHA KECIL DAN MENENGAH PADA PT BANK NEGARA INDONESIA TBK (BNI) KANWIL SURABAYA - HANDAYANI, ANNISA (Jurnal Akuntansi AKUNESA, 2012)
The implementation of People’s Business Credit risk, credit congestion is a problem affecting the health of banks. Therefore, we need an execution control system to assess internal controls and to know the policy of the bank's management in their performing duties. This research was conducted with the aim to evaluate the Internal control system BNI with existing theories. The research result shows that the system adopted in the micro credit lending process has already most of the elements of internal control, BNI has an adequate internal control structure of the credit for preventing abuse of authority.Key word : Internal control system, credit